Tajemnice narracji pierwszoosobowej czyli periplus w Dziejach Apostolskich - Wojciechowska, Kalina (Biblica et Patristica Thoruniensia, 2014)
The Acts of the Apostles cointain thepassages in the firstperson pluralnarration–16,10-17;20,5-15;21,1-18;27,1–28,16. Thepresenceof this narration coincidences with a sea voyages. Sea journey appears often in Greek and Romanliterature–so for example in Homer’s Odyssey,in works of Alcaeus,Mimnermos,Vergil,Petronius,Lucian,Heliodor. Oneof the primary features of this genre–theso-called periplus–is the presence of firstperson plural narration;other features are: the beginning of the sailing,halting places of the journey,landing at the places,meeting with local inhabitants and resuming the voyage. Theauthor of Luke-Acts employs his periplus with great skill and uses firstperson pluralas the stylistic componentof this genre. However,the first person plural narration in the Acts makes often a transition to third person narration or to a speech. The third person narration and a speech within the“we-passage” are a kind of the excurses. The third person narration appears also in the episodes recounting Paul’s overland travels;these episodes belong to the main action. The usageof the first and the third person narration according to the generic convention suggests that the author of Luke-Acts is a versatile Hellenistic writer who is an intelligent participantin the literary arena of Mediterranean culture.